Interdependence between geometric, tensile and chemical bond behaviours of untreated hair fibres - Cloete, Elsabe (Department of Medicine, 2021)
To date, an accurate understanding of the dynamics between the fibre's inherent geometric, mechanical and biological characteristics is deficient, affecting the reliability and robustness of hair data. There is also insufficient scientific clarity on the behaviour of curly hair, as most of the conclusions have been drawn from studies focusing on straight fibres. This research project aimed at gaining a more accurate understanding of the interrelationships between fibre curliness, strength and chemical bonding. In the current understanding of hair mechanics, curly fibres are considered to have a lower tensile strength than straight fibres. Furthermore, the current understanding of hair fibres does not associate hydrogen bonding with fibre shape. During experimentation, inadvertent observations suggested that current tensile methods ignore an important component of hair strength in curly fibres, and that hydrogen bonding supports fibre curliness. Intensive scrutiny of these observations led to fundamental contributions to the understanding of curly hair. Research tools included tensile, geometric, image, (FTIR) spectroscopic assessments, regression modelling and multivariate statistical analysis. Through this research, the role of hydrogen bonding in fibre curliness has been established. A theory is presented about extraordinary hydrogen bonds and the existence of hydrogen bond networks across the fibre matrix of curly hair. The theory has been substantiated experimentally via FTIR and weight measurements. The research also established the importance of the preelastic tensile region for curly fibres. It was clearly demonstrated that tensile strength of hair fibres is not only dependent on Young's modulus, but also on the fibre's inherent viscoelasticity, which appears to be important in curly fibres but becomes negligible with loss of curl. A model, developed from experimental observations and insights from similar biological fibres, is also presented. The model gives insights into ultrastructural changes at the early onset of fibre elongation. It also demonstrates the association between viscoelasticity and hydrogen bond networks. Taking this into consideration, a constitutive equation, developed to determine hair fibre strength accurately, is also presented in this work. This work does not replace current fibre curvature theories, but provides additional insights into hair shape, and therefore presents a fundamental contribution to curvature in human hair. It also highlights the shortcomings of current instrumentation methods that contribute to inaccurate conclusions regarding the strength of curly fibres.